ORGANIC COMPONENTS OF ANTARCTIC SNOW AND ICE : PART 1. VOLATILE FATTY ACIDS IN SNOW DRIFT - オオタ, ケイイチ; ニシオ, フミヒコ; オサダ, カズオ; OHTA, Keiichi; NISHIO, Fumihiko; OSADA, Kazuo (National Institute of Polar Research, 1990)
P(論文) Snow drift samples collected on Mizuho Plateau, Antarctica, were analyzed for volatile fatty acids including formic, acetic, propionic and butyric acids. Formic (2.3-11.7 ppb) and acetic (11.4-59.8 ppb) acids were detected as major components. Their concentrations were far lower than those reported in rain and snow samples from urban, rural and remote areas. However, the concentrations were higher than those of formic and acetic acid concentrations reported in the ice core sample collected from the coast of East Antarctica. The concentrations of volatile fatty acids in snow drift samples showed a marked seasonal variation, i. e., low levels in winter and high levels in summer, correlating with solar radiation. Based on this seasonal variation, we concluded that these volatile fatty acids were produced by photochemical oxidation of atmospheric hydrocarbons. The contribution of these volatile fatty acids to the acidity of snow drift was indicated to be small. departmental bulletin paper